Application of phytoimmunostimulant food to the hematology of common carp (Cyprinus carpio) preserved in brackish water - Nasution, Nisfi Maulidia; Effendi, Irwan; Batubara, Ummi Mardhiah (South East Asian Marine Sciences Journal, 2025)
This research was conducted from October to December 2023 at the Marine Microbiology Laboratory, Faculty of Fisheries and Marine Sciences, University of Riau. This study aimed to analyze the effect of adding guava leaves (Psidium guajava) on the hematology of common carp (Cyprinus carpio) reared in brackish water infected with Aeromonas hydrophila. The method used was an experiment with a Completely Randomized Design (CRD) of one level, the concentration of phytoimmunostimulant administration with five treatment levels and three replications, namely, P0 (commercial pellets), the addition of guava leaf flour dose P1 (1.0 g / 100 g feed), P2 (1.5 g / 100 g feed), P3 (2.0 g / 100 g feed), P4 (2.5 g / 100 g feed). Based on the study's results, it is known that adding guava leaf flour to common carp feed reared in brackish water media and challenged with A. hydrophila bacteria shows a significant effect (P < 0.05). The best dose was obtained in P2 (1.5 g/100 g feed) with the number of erythrocytes 1.54-1.63x106 cells/mm3, hemoglobin 5.93-7.80 g/dL, and hematocrit 30.33-37.67